Global Health in International Relations: State Actors' Response to COVID-19 - Dzikiara Pesona Sadewa (Jurnal Lemhannas RI, 2024)
Purpose: This study seeks to explore the role of states in managing the COVID-19 pandemic by examining two key perspectives: the Statist and the Globalist approaches. It further emphasises how these approaches can complement each other in addressing global health challenges effectively. Study Design/Methodology/Approach: The study adopts a qualitative methodology, analysing literature from academic articles, policy reports, and publications by international health organisations. This method enables a thorough examination of the strategies employed by various states in response to the pandemic. Findings: The research identifies that the Statist approach prioritises national-level measures, such as strengthening healthcare infrastructure, enforcing lockdowns, and developing vaccines to ensure state stability. Conversely, the Globalist perspective highlights the critical role of international collaboration, equitable vaccine distribution, and shared health governance. The findings underline that integrating these two approaches is pivotal for developing a robust response to global health crises. Originality/Value: This study offers new perspectives within the field of international relations by analysing the interaction between Statist and Globalist strategies in managing pandemics. It underscores the importance of harmonising these approaches to address cross-border health challenges more effectively in the future.